Coexistent Nodal Diffuse Large B-Cell Lymphoma With Extrapulmonary Tuberculosis: A Rare Case. (February 2016) - Sachdev, Ritesh; Duggal, Rajan; Agrawal, Krati; Goel, Shalini
Extrapulmonary tuberculosis coexistent with lymphomas in the same organ are rare and have been reported in the literature. The most common organs that are involved are small bowel, bronchus, kidney, and lymph nodes. Interestingly, the lymphoma that is commonly present with extrapulmonary tuberculosis is Hodgkin's lymphoma followed by low-grade non-Hodgkin's lymphoma. In the present study, we report a 60-year-old man with complaints of fever, loss of appetite, and generalized weakness. On investigation, generalized lymphadenopathy was noted, and the biopsy of cervical lymph node revealed coexistence of diffuse large B-cell lymphoma with extrapulmonary tuberculosis. This case is the second reported case of diffuse large B-cell lymphoma with extrapulmonary tuberculosis in the world and the first in India.